y =1/4x - 4 : y = -7/4x + 4 I need help with this one...has to be solved by elimination. Thanks

multiply 1st eqn by 7 add to 2nd eqn to eliminate x solve for y , then substitute back to find x

y = y 1 / 4 x - 4 = - 7 / 4 x + 4 Add 7 / 4 x to both sides 1 / 4 x - 4 + 7 / 4 x = - 7 / 4 x + 4 + 7 / 4 x 8 / 4 x - 4 = 4 2 x - 4 = 4 Add 4 to both sides 2 x - 4 + 4 = 4 + 4 2 x = 8 Divide both sides by 2 x = 8 / 2 x = 4 Replace this value in equation for y. y = 1 / 4 x - 4 = x / 4 - 4 = 4 / 4 - 4 = 1 - 4 = - 3 OR y = - 7 / 4 x + 4 = - 7 ∙ x / 4 + 4 = - 7 ∙ 4 / 4 + 4 = - 7 + 4 = - 3 Solution: x = 4 , y = - 3 You can write this as: ( 4 , - 3 )

-x/4 + y = -4. Standard form. Multiply both sides by 4: Eq1: -x + 4y = -16. 7x/4 + y = 4. Multiply both sides by 4: Eq2: 7x + 4y = 16. Multiply Eq1 by -1 and add Eq1 and Eq2: x - 4y = 16 7x + 4y = 16 Sum: 8x = 32 X = 4. In Eq1, replace X with 4 and solve for Y: -4 + 4y = -16. Y = -3.

First Name

Your Response